Flexopiezoelectricity at ferroelastic domain walls in WO3 films - Shinhee Yun (Nature Portfolio, 2020)
Observation of a strain-gradient-induced piezoresponse at domain walls remains a challenge. Here, the authors find the piezoelectric response to be enhanced in the ferroelastic domain walls of centrosymmetric tungsten trioxide thin films due to a large strain gradient over a wide width of the wall.